EVALUATION OF DETERMINANTS OF DIVIDEND PAYOUT RATIO CASE STUDY: LQ45 COMPANIES STOCKS (2014-2018) (The Indonesian Journal of Business Administration, 2021)
The purpose of this research is to determine whether there is an effect of Liquidity, Leverage, Firm Size, Growth Opportunity, and Profitability toward Dividend Policy. The proxies used are Current Ratio (CR) for Liquidity, Debt to Equity Ratio (DER) for Leverage, Firm Size, Growth, Return on Assets (ROA) for Profitability and Dividend Payout Ratio (DPR) for the Dividend Policy of the company. The population of this study is companies listed in the LQ-45 Index from the period of 2014 to 2018. This study uses a purposive sampling method with criteria consist of companies that consistently listed on LQ-45 index period of 2014-2018, non-financial institution companies since the financial institution industry has a specific characteristic in the financial report, and companies that publicly exposed the financial report from the period of 2014 to 2018 and have all the data required for this research. Based on aforementioned criteria, there are 25 companies taken as samples and the subject for this study. The analytical techniques used in this research consist of selection of regression panel data model, descriptive statistics analysis, classical assumption test, multiple liner regression test, and hypothesis test comprising an analysis of the coefficient of determination, partial test (statistical test of t), and model group test (statistical test of f). The result indicates that only Growth Opportunity and Return on Assets (ROA) that have significant effect on Dividend Payout Ratio.Keywords: Liquidity (CR), Leverage (DER), Firm Size, Growth Opportunity, Profitability (ROA) and Dividend Policy (DPR)